Sistem Informasi Keuangan Sidoarjo (SIKSDA) dalam Peningkatan Tata Kelola Keuangan Publik dan Pembangunan Ekonomi Sidoarjo. - Purwita, Febria Ayu; Lathifah, Nurul (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine how the Regional Financial Information System (SIKSDA) is used to improve local government financial management and stimulate economic growth in Sidoarjo Regency. To this end, the author used qualitative methods by conducting in-depth interviews, direct observation, and analyzing various related documents. The results indicate that SIKSDA has helped improve transparency, accountability, and efficiency in managing regional finances, thus having a positive impact on local economic development. However, several issues remain, such as a lack of human resources and adequate technological facilities, which need to be addressed for SIKSDA to function optimally. This study also provides several strategic recommendations to local governments in improving and developing SIKSDA for more effective use.